2020
DOI: 10.1039/d0ra00154f
|View full text |Cite
|
Sign up to set email alerts
|

Biocorrosion of pure and SLA titanium surfaces in the presence of Porphyromonas gingivalis and its effects on osteoblast behavior

Abstract: The study demonstrated that P. gingivalis could colonize on pure and SLA titanium surfaces and weaken their surface properties, especially the protective TiO2 film, which induced the biocorrosion and further negatively affected osteoblast behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 46 publications
(55 reference statements)
1
5
0
Order By: Relevance
“…41 Studies showed the increase of the corrosion rate and the damage of oxide lm according to the electrochemical tests and SEM images in the presence of oral bacteria. 42,43 Hanawa et al studied the Fig. 1 Various corrosions of dental implants cause the release of metal ions.…”
Section: Titanium Ionsmentioning
confidence: 99%
See 1 more Smart Citation
“…41 Studies showed the increase of the corrosion rate and the damage of oxide lm according to the electrochemical tests and SEM images in the presence of oral bacteria. 42,43 Hanawa et al studied the Fig. 1 Various corrosions of dental implants cause the release of metal ions.…”
Section: Titanium Ionsmentioning
confidence: 99%
“… 41 Studies showed the increase of the corrosion rate and the damage of oxide film according to the electrochemical tests and SEM images in the presence of oral bacteria. 42,43 Hanawa et al studied the regeneration of the oxide film on titanium surfaces and predicted the release of titanium ions when the oxide film was destroyed. 44 The release of titanium ions affects the integration of the titanium implant with the bone and can eventually cause the implant to fall off due to poor bone integration.…”
Section: Adverse Effects Of Metal Ions On Implant Osseointegration An...mentioning
confidence: 99%
“…This results from Ag ions being unable to kill S. mutans and strengthen oral hygiene and protection. (4) S. mutans is a strong acid-producing (acidogenic) bacterium that produces observable dental plaque, thereby triggering demineralization and decay. (5) Additionally, metallic materials are damaged by microbiologically induced corrosion, which is a major concern in many fields.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies found that suspected pathogenic bacteria such as Porphyromonas gingivalis and Actinobacillus could colonized on the surface of Ti. Their metabolites reduced the local pH value in a short time, destroyed the oxide film on the surface of Ti, and caused corrosion and release of Ti ions (Xu, Yu, Chen, Zhang, & Qiu, 2020;Zhang et al, 2013). Besides microbial corrosion, many corrosion types exist around the Ti implant, such as stress corrosion, osteoclast corrosion, oxidative corrosion, pitting corrosion, fretting corrosion, and so on, which affect and promote each other, eventually leading to the release and aggregation of Ti ions (Cadosch et al, 2010;Golvano, Garcia, Conde, Tato, & Aginagalde, 2015;Zhu et al, 2019).…”
Section: Introductionmentioning
confidence: 99%